ON THE NATURE OF MANTLE HETEROGENEITIES AND DISCONTINUITIES: EVIDENCE FROM A VERY DENSE WIDE-ANGLE SHOT RECORD - Carbonell R. (My University, 2004)
A seismic survey with a receiver spacing of 50 m provided one of the most densely sampled wide-angle seismic reflection images of the lithosphere. This unique data set, recorded by an 18-km-long spread, reveals that at wide-angles the shallow subcrustal mantle features high amplitude reflectivity which contrasts with a lack of reflectivity at latter travel times. This change in the seismic signature is located at approximately 120–150 km depth, which correlates with the depth estimates of the lithosphere–asthenosphere boundary (LAB) of previous DSS studies. This seismic signature can be simulated by two-layer mantle model. Both layers with similar average velocities differ in their degree of heterogeneity. The shallow heterogeneous layer and the deeper and more homogeneous one correlate with the lithosphere and the asthenosphere, respectively. Studies involving surface outcrops of ultramafic massifs and mantle xenoliths infer that the upper mantle is a heterogeneous mixture of ultramafic rocks (lherzolites, harzburgites, pyroxenites, peridotites, dunites, and small amounts of eclogites). Laboratory measurements of physical properties of these mantle rocks indicate that compositional variations alone can account for the wide-angle reflectivity. A temperature increase would homogenize the mixture, decreasing the seismic reflection properties due to melting processes. It is proposed that this would take place below 120–150 km (1200 °C, the LAB).
Keywords: Wide-angle seismic reflection; Petro-physical model; Uralides; Lithosphere–asthenosphere boundary